If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g(x) = x + 14 Multiply g * x gx = x + 14 Reorder the terms: gx = 14 + x Solving gx = 14 + x Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Divide each side by 'x'. g = 14x-1 + 1 Simplifying g = 14x-1 + 1 Reorder the terms: g = 1 + 14x-1
| 2345678347756846876427867478968763276878684348237682764878736+73642675682385678482486747= | | g(y+6)= | | (3x-1)/4-2x+1/5=(7x-13)/20 | | 32+5=2x+13 | | 0=1.5x^2-8x+8 | | 2x+4x+3y-y= | | -3m+1=9-15 | | 104=2(x+16)+x | | r=1/3d(60-t) | | -5x-4=16+x | | 2x+40=4x+22 | | D(t)=4.9t^2-0.1t^3 | | 8x+204=6x+180 | | |2-5|= | | 3(2n+4)=30 | | 6x-16=104 | | 7-9z=81+z | | 4x^2-19x+17=-6x+7 | | 4r+(7*4)=72 | | 3a-5=18 | | F(x)=4x-3x^2-x^3 | | D(t)=4.9t^2 | | 2-(3x-20)=11-10x | | =x(24-2x)(45-2x) | | x^2+y^2-7x-7y+12=0 | | 3x-2/8=40 | | 15x-15x=12 | | 2(3t-4)=10t-7 | | 6-7x=5x-9x+6 | | 9x-27=8x-7 | | 4n^2+4n-35=0 | | 4y+1Y= |